Efektivitas Pendekatan Contextual Teaching And Learning Berbasis Questioning Terhadap Keterampilan Bertanya dan Hasil Belajar Siswa Kelas V Mata Pelajaran IPA MI NW Rekat Lauk Tahun Pelajaran 2019/2020 - Wardani, Rinayati (FAKULTAS TARBIYAH, 2020)
Educational goals must be supported by an effective and efficient learning process. The effective learning process carried out by students in schools is not only determined by the degree of ownership of the potential of the students concerned but also by the environment, especially professional teachers. There is a tendency that a pleasant attitude, the warmth of brotherhood, not scary or the like, is seen by some people as good teachers. However, learning is obtained monotonously so science learning which aims to develop students' thinking skills has not materialized. The achievement of questioning skills and student learning outcomes with the CTL (contextual teaching learning) approach is higher than with the lecture method. The application of the CTL approach has an influence on questioning skills and student learning outcomes at MI NW Rekat Lauk. This can be seen from the average score of student learning outcomes in the posttest group in the experimental class 79. Meanwhile, in the pretest group, the test score for learning outcomes was 69. For hypothesis testing, the t-test was used. The results of the t-test on the post-test results obtained tcount> t table (11.26>1.729) at a significant level = 0.05 with dk = 38, which means that there are differences in learning outcomes between the pretest group and the posttest group in the experimental class according to the hypothesis proposed in this study. Meanwhile, the average score of the post-test observation sheet questioning skill was obtained t_count> from t_table (7.26> 2,024). This indicates that the student's ability to ask questions is good. This indicates that student learning outcomes in the post-test experimental class group that apply the CTL approach show that questioning skills and student learning outcomes increase, which means that there is a significant influence in the CTL approach on questioning skills and student learning outcomes in class V MI NW Rekat Lauk